1992
DOI: 10.1136/ard.51.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of inherited factors to rheumatoid arthritis.

Abstract: A total of 231 sibships of the same sex (186 female, 45 male), in which the proband had classical or definite rheumatoid arthritis (RA) have been selected from rheumatology clinics. Each sibship member was questioned about symptomatic joints, which were then examined. Hospital records, radiographs, and rheumatoid factor measurements aliowed each sibling to be classified as having classical, definite, probable, or no RA. Each sibling was typed for HLA-A and B and was classified as sharing two, one, or zero HLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 4 publications
1
22
0
3
Order By: Relevance
“…Recent studies in RA patients have emphasized that HLA-DR molecules function as progression factors and may not be involved in the initiation of the disease [17]. Genotyping of large cohorts of RA patients as well as concordance studies in RA families indicated that disease associated HLA-DRB 1 alleles were frequently inherited on both haplotypes [18][19][20]. In a peptide binding model, heterozygosity for the relevant MHC molecule should be sufficient to ascertain antigen selection and presentation.…”
Section: Hla Genes and Disease Risk In Ramentioning
confidence: 99%
“…Recent studies in RA patients have emphasized that HLA-DR molecules function as progression factors and may not be involved in the initiation of the disease [17]. Genotyping of large cohorts of RA patients as well as concordance studies in RA families indicated that disease associated HLA-DRB 1 alleles were frequently inherited on both haplotypes [18][19][20]. In a peptide binding model, heterozygosity for the relevant MHC molecule should be sufficient to ascertain antigen selection and presentation.…”
Section: Hla Genes and Disease Risk In Ramentioning
confidence: 99%
“…Findings from genetically identical twins, where the concordance rate is far less than complete, are indicative for a major role of an environmental factor in the risk of developing RA. 9,10 From animal models it is clear that an exogenous challenge, like infectious agents may induce arthritis. In man, microbial infections are known to contribute to arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…The healthy control group consisted of 116 unrelated Caucasian women without autoimmune disease from the same geographic regions in Northern California. The study subjects were restricted to Caucasian females to minimize heterogeneity in allelic frequencies across populations, and because RA risk and disease expression are likely to differ between males and females [Deighton et al, 1992;Weyand et al, 1992a;Hasstedt et al, 1994;Meyer et al, 1996].…”
Section: Subjects and Methods Patientsmentioning
confidence: 99%